Evaluation and analysis of multidrug resistance- and hypervirulence-associated genes in carbapenem-resistant Pseudomonas aeruginosa strains among children in an area of China for five consecutive years - Zhang, Xin; Zhu, Yunfen; Gao, Yuanyuan; Li, Wei; Wang, Yunzhong; Li, Yang (Frontiers in Microbiology, 2023)
Carbapenem-resistant Pseudomonas aeruginosa (CRPA) is a growing threat. It is urgent to investigate the multidrug resistance and high virulence of CRPA to provide a basis for infection control and rational use of antibiotics. A retrospective study of 56 nonduplicated CRPA isolates was conducted. In this work, CRPA mainly came from the intensive care unit (ICU) and was mostly isolated from sputum samples. The carbapenem resistance rates of P. aeruginosa were 21.37% (2016), 10.62%, 5.88%, 10% and 13.87% from 2016 to 2020, respectively. Carbapenem-resistant enzymes and aminoglycoside-modifying enzyme-encoding genes were detected in all isolates, and extended-spectrum β-lactamase and cephalosporin enzyme-encoding genes were present in 96.43% and 80.38% of isolates, respectively. The detection rate of OprM showed a statistically significant difference (P<0.05) between the ICU and other wards. Genes related to biofilms, membrane channel proteins, I integrons and efflux systems were detected in all isolates, with detection rates greater than 90%. CRPA was strongly virulent, and over 80% of isolates carried hypervirulence-associated genes (exoU, exoS, exoT and exoY). The drug resistance rates of cefepime and piperacillin/tazobactam showed a statistically significant difference (P<0.05) between strains with exoU (+) and exoU (-) (P<0.05). Notably, out of the 7 individuals who died, 4 had extensively drug-resistant P. aeruginosa (57.14%). The detection rates of various resistance and virulence genes were high, and the coexistence phenomenon was serious. In clinical practice, antibiotics should be used reasonably based on different drug resistance genes to ensure the rationality and safety of patient medication.